2003
DOI: 10.1073/pnas.2136632100
|View full text |Cite
|
Sign up to set email alerts
|

Network component analysis: Reconstruction of regulatory signals in biological systems

Abstract: High-dimensional data sets generated by high-throughput technologies, such as DNA microarray, are often the outputs of complex networked systems driven by hidden regulatory signals. Traditional statistical methods for computing low-dimensional or hidden representations of these data sets, such as principal component analysis and independent component analysis, ignore the underlying network structures and provide decompositions based purely on a priori statistical constraints on the computed component signals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
697
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 554 publications
(698 citation statements)
references
References 20 publications
1
697
0
Order By: Relevance
“…PPARs are transcription factors of the nuclear receptor superfamily, and regulate gene expression of various genes (including GK) in response to fatty acids [54,55]. Our previous study [2] showed, by using transcriptome profiling and network component analysis [56], that GK deletion affects the transcription factor activity of PPARα, SREBP1c, and SREBP2 in mouse liver. Further, a PathwayAssist analysis revealed that GK is closely linked to PPARα and SREBPs [2].…”
Section: Discussionmentioning
confidence: 99%
“…PPARs are transcription factors of the nuclear receptor superfamily, and regulate gene expression of various genes (including GK) in response to fatty acids [54,55]. Our previous study [2] showed, by using transcriptome profiling and network component analysis [56], that GK deletion affects the transcription factor activity of PPARα, SREBP1c, and SREBP2 in mouse liver. Further, a PathwayAssist analysis revealed that GK is closely linked to PPARα and SREBPs [2].…”
Section: Discussionmentioning
confidence: 99%
“…Network Component Analysis-NCA is an algorithm that deduces system structure from sparsely connected networks, such as transcriptional regulatory networks (27,28). Other bipartite network analysis methods have been applied to biological data, such as a probabilistic state-space model (29) and an integration of expression and TF binding data (30).…”
Section: Methodsmentioning
confidence: 99%
“…NCA is a mathematical approach that employs biologically relevant constraints to identify perturbed regulators in transcriptome data by accounting for regulator activity and separating the effects of multiple regulators (27,28). Many TFs have both an active and an inactive state, where only the active state is able to affect transcript abundance.…”
Section: Gsno and No Inhibit Growth Through Distinct Mechanisms-mentioning
confidence: 99%
“…Here, we report the use of network component analysis (NCA) recently developed in our group (1) to determine the dynamics of the activities of various TFs during a physiological process. This approach uses both DNA microarray data and partial information regarding the membership of regulons as defined by each TF in question.…”
mentioning
confidence: 99%